Effects of Air-side Structure on Heat Transfer and Flow Performance of Multiple Micro-channel Parallel Flow Condenser - Gu Bo; Fang Jihua; Zhao Pengcheng (Zhileng xuebao)
The theoretical model of the multiple micro-channel parallel flow condenser is established based on the method of distribution parameters, and validity of the model is verified by comparison with the experimental data. Based on this model, the effects of fin height, fin pitch, louver pitch and louver angle on the heat transfer and flow performance of multiple micro-channel parallel flow condenser are investigated. The results show that, as increasing of fin height, the heat transfer rate increases, but the air-side pressure drop decreases; when fin pitch increases, or louver pitch increases, the heat transfer rate and air-side pressure drop all decrease; as increasing of louver angle, the heat transfer rate and air-side pressure drop all increase.